High Electrical Conductivity and Low Temperature Resistant Double Network Hydrogel Ionic Conductor as a Flexible Sensor and Quasi‐Solid Electrolyte. Issue 45 (1st December 2022) - Ma, Xudong; Maimaitiyiming, Xieraili
Abstract: The existence of large amounts of water in hydrogel electrolytes makes them inevitably freeze at low temperatures, which causes them to lose properties such as flexibility or electrical conductivity. It limits the application of hydrogel electrolytes at low temperatures. Here, we designed hydrogels with interpenetrating double network structure based on polyacrylamide and agar. By doping a high concentration of LiCl as the conducting material, a continuous ion‐conducting path was formed. The conductivity reached 2.18 S/m at 25 °C and 1.58 S/m at −30 °C. The prepared hydrogel electrolytes exhibit good mechanical and electrochemical properties to meet the needs of different application situations. A wearable sensor with hydrogel electrolytes was demonstrated. The wearable sensor can be attached to a part of the human body and can successfully detect various human movements. The wearable sensors can be used as temperature sensors in addition to detecting motion, which shows an encouraging and powerful utility in wearable electronic devices. Abstract : A conductive multifunctional hydrogel for flexible wearable devices and quasi‐solid electrolytes was prepared. The assembled flexible sensor can detect human pulse and temperature. The hydrogel‐based supercapacitor possesses good electrochemical performance after 4000 cycles at −30 °C. The assembled hydrogel‐based supercapacitor maintained good capacitance retention after bending at different angles. (0°; 90°; 180°)